Aplicação foliar de tiossulfato de amônio e metileno ureia associado a fungicida em soja e sua interferência no patossistema Glycine max - Phakopsora pachyrhizi - Minuzzi, Simone Gripa (2018)
Asian soybean rust (ASR), caused by Phakopsora pachyrhizi, is the main disease on soybean crop and can cause important yield reduction. The chermical control is the most suitable for a disease like ASR. However, due to the constant reduction of their efficacy, the adoption of integrated management control of ASR has been widely discussed for the soybean sustainability. These measures include the use of foliar fertilizers to increase disease control. The studies aimed to elucidate the effects of nitrogen and / or sulfur leaf fertilizers isolated and associated with a commercial fungicide composed by picoxystrobin + cyproconazole on the of ASR control and, as well as the biochemical responses of the plants exposed to these treatments, as well as the yield effect under different growing environments. Field trials were conducted in greenhouse and field, divided in three chapters. The first study considered the effect of the use of ammonium thiosulfate and methylene ureas in the cultivars NS 5445, BMX Tornado and TMG 7062 was investigated based on biochemical parameters, enzyme activation, lipid peroxidation and phenolic compound concentration, and control. From this it was verified that the foliar fertilizers reduced the oxidative stress of the plants under infection of P. pachyrhizi, besides providing control of the disease. The first biochemical evidence of the great activation of phenylalanine ammonia lyase and high lipid peroxidation in cultivar TMG 7062 was identified. The second study considered the effect of the association of foliar fertilizers with the pre-mixture fungicide based on picoxystrobin + cyproconazole was also investigated, based on the biochemical parameters mentioned above, and its effect of disease control. The pre-mixture fungicide induced great oxidative stress in the plants of the three cultivars and the associations with the fertilizers overall did not alleviate the damage in the lipid membranes nor led to the activation of evaluated routes of defense. However, they increased the FAS control, thus presuming a toxic effect on the fungus through the deposition of chemical elements on the leaf surface, preventing the germination and colonization of the fungus in the foliar tissues. The third study analized the effect of the isolated and associated foliar fertilizers to the pre-mixture fungicide on ASR under different cropping environments (Itaara/RS and Planaltina/DF) within the established control program. In order to determined such association it was evaluated the severity of ASR, yield and thousand seed mass in the different treatments and under two cultivars, NS 5445 and BMX Tornado. It was verified that, under conditions of low disease pressure (Planaltina), the associations of picoxystrobin + cyproconazole with foliar fertilizers increased ASR control, but under high disease pressure (Itaara) they did not have any control increments within the established control program. New information regarding the recent use of ammonium thiosulfate and methylene urea, which may contribute to the definition of strategies for the management of ASR is presented.